Identification and Percentage of Disease Pathogen Attacks on Primary Palm Oil Crops: Elaeis Guineensis Jacq - Defitri, Yuza; Marcelian, Sherly (Journal of Agriculture, 2023)
The aim of this research is to identify and determine the percentage of diseases caused by fungi in oil palm seedlings. The purposive sampling method and the objects observed were fungi that cause disease in oil palm seedlings microscopically at the Jambi Class 1 Agricultural Quarantine Laboratory. The results of the research found that Curvularia sp disease had a percentage of attacks in nursery one (f?) of 25%, while the intensity of attacks in nursery one (f?) was 5%, in nursery two (f?) the percentage of attacks was 25% while the intensity of attacks in nursery two (f?) 6%, and in the third nursery (f?) the attack percentage was 10%, while the attack intensity in the third nursery (f?) was 2%. The percentage of attacks by Pestalotiopsis sp in nursery one (f?) is 20%, while the intensity of attacks in nursery one (f?) is 4%, in nursery two (f?) the percentage of attacks is 5%, while the intensity of attacks in nursery two (f?) is 1%, and in nursery three (f?) attack percentage was 20% while the attack intensity in the three (f?) nursery was 4%. From this research, it was concluded that two diseases were found in oil palm seedlings, namely Curvularia sp leaf spot and Pestalotiopsis sp leaf spot.